ChemInform Abstract: Diterpenes with Unprecedented Skeletons from the Red Alga Sphaerococcus coronopifolius. Issue 36 (September 2015) - Smyrniotopoulos, Vangelis; Kiss, Robert; Mathieu, Veronique; Vagias, Constantinos; Roussis, Vassilios
Abstract Three new diterpenes, namely spirosphaerol (I), anthresphaerol (II), and corfusphaeroxide (III) are isolated and structurally characterized by NMR and MS and their in vitro antitumor activities against human cancer lines tested.